2018
DOI: 10.1177/0255761418771094
|View full text |Cite
|
Sign up to set email alerts
|

A cosmopolitan culture-bearer as activist: Striving for gender inclusion in Nepali music education

Abstract: Although music education scholars have increasingly advised teachers to take heed of values, principles, and strategies of musical practices outside of school, very little has been written in music education regarding the ideological underpinnings of musical practices in these contexts. This article argues that musical practices outside of school do not necessarily provide ideal models to be directly applied in the music classroom, but need to be critically examined and transformed to better align with global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…(Figure 6). Such enhanced reflexivity was also witnessed in an activist culture-bearer's work in Nepal for enhancing girls' participation in music education (Westerlund & Partti, 2018) and in an all-female Ultra-Orthodox Jewish music teacher education programs in Israel . The reflexive work in these studies does not fall into the category of content knowledge, but is more related to devising sustainable and ethical strategies in changing community attitudes as well as navigating through and against established exclusive traditions.…”
Section: Expanding Perspectives Of Co-constructed Futures and Reflexive Intercultural Music Teacher Educationmentioning
confidence: 89%
“…(Figure 6). Such enhanced reflexivity was also witnessed in an activist culture-bearer's work in Nepal for enhancing girls' participation in music education (Westerlund & Partti, 2018) and in an all-female Ultra-Orthodox Jewish music teacher education programs in Israel . The reflexive work in these studies does not fall into the category of content knowledge, but is more related to devising sustainable and ethical strategies in changing community attitudes as well as navigating through and against established exclusive traditions.…”
Section: Expanding Perspectives Of Co-constructed Futures and Reflexive Intercultural Music Teacher Educationmentioning
confidence: 89%
“…The theoretical background for this study is found in new opera studies (see Johnson, 2007;Levin, 2007;Till, 2012;Novak, 2015), which underlines theoretical and methodological interdisciplinarity, and follows Till's perspective (2012, p. 2): "To study opera we have to study more than opera". Having interdisciplinarity as my Leitmotiv, I will utilise three theoretical approaches: narrative research (Atkinson, 1998;Leavy, 2011;Westerlund & Partti, 2018), professionalism studies , and sociology of music (DeNora, 2002(DeNora, , 2011.…”
Section: Oral History As a Methodologymentioning
confidence: 99%
“…Henderson, 2003; Moisala, 1999; Stirr, 2010, 2018; Tingey, 1992, 1993; Widdess, Wegner, Tingey, & Moisala, 2001), while studies of music education in Nepal have highlighted activist practices aimed at increasing female access and participation (e.g. Shah, 2018; Tuladhar, 2018; Westerlund & Partti, 2018). During my first visits to the Kathmandu Valley in 2014, the school administrators, teachers and musician-teachers I encountered were almost exclusively male.…”
Section: Mode Of Inquirymentioning
confidence: 99%